2002
DOI: 10.1677/joe.0.1750201
|View full text |Cite
|
Sign up to set email alerts
|

Natural (ghrelin) and synthetic (hexarelin) GH secretagogues stimulate H9c2 cardiomyocyte cell proliferation

Abstract: Recent experimental data demonstrate cardiovascular effects of the GH secretagogues (GHSs) hexarelin and ghrelin, the proposed natural ligand for the GHS receptor. Moreover, specific cardiac binding sites for GHSs have been suggested. The aim of the present study was to investigate if the natural ligand ghrelin and synthetic GHS peptide hexarelin and analogues have direct effects on the cardiomyocyte cell line, H9c2. Hexarelin stimulated thymidine incorporation in a dose-dependent manner with significant respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
1
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 56 publications
5
57
1
2
Order By: Relevance
“…This pattern of expression is in agreement with the proposed role for ghrelin in the autocrine/paracrine control of cell proliferation and cancer. Proliferative actions of ghrelin (or its synthetic analogs, the GHSs) are observed in prostate (PC-3) and thyroid (anaplastic carcinoma; ARO) cancer cell lines as well as the cardiomyocyte H9c2 cell line and cultured adrenocortical cells , Pettersson et al 2002, Andreis et al 2003, Jeffery et al 2003. Conversely, anti-proliferative effects of ghrelin/GHSs are observed in several thyroid (papillary carcinoma; NPA, follicular carcinoma; WRO), lung (CALU-1), and breast (MCF7, T47D, MDA-MB231) cancer cell lines , Ghe et al 2002 as well as in immature Leydig cells of the testis .…”
Section: Human Datamentioning
confidence: 99%
“…This pattern of expression is in agreement with the proposed role for ghrelin in the autocrine/paracrine control of cell proliferation and cancer. Proliferative actions of ghrelin (or its synthetic analogs, the GHSs) are observed in prostate (PC-3) and thyroid (anaplastic carcinoma; ARO) cancer cell lines as well as the cardiomyocyte H9c2 cell line and cultured adrenocortical cells , Pettersson et al 2002, Andreis et al 2003, Jeffery et al 2003. Conversely, anti-proliferative effects of ghrelin/GHSs are observed in several thyroid (papillary carcinoma; NPA, follicular carcinoma; WRO), lung (CALU-1), and breast (MCF7, T47D, MDA-MB231) cancer cell lines , Ghe et al 2002 as well as in immature Leydig cells of the testis .…”
Section: Human Datamentioning
confidence: 99%
“…In particular, peptidyl GHS, such as hexarelin, improve the post-ischemic recovery of hearts of either aged or GH-deficient rats and increase left ventricular ejection in patients with severe GH-deficiency (Bisi et al, 1999;Imazio et al, 2002). A stimulatory effect on cell proliferation (Pettersson et al, 2002) and an antiapoptotic action (Filigheddu et al, 2001) of GHS on the cardiomyocyte cell line H9c2 have also been shown. The natural ligand of the GHS type 1a receptor has more recently been discovered as a gastric-derived hormone named ghrelin (Kojima et al, 1999).…”
Section: Introductionmentioning
confidence: 96%
“…At the functional level, n-octanoylated ghrelin treatment increases the rate of proliferation in a number of cell lines, including human prostate cancer (Jeffery et al 2002), HepG2 hepatoma (Murata et al 2002) and pancreatic adenocarcinoma cancer cell lines (Duxbury et al 2003), rodent pituitary tumour cells (Nanzer et al 2004), as well as some normal cell lines and primary cell cultures (Pettersson et al 2002, Andreis et al 2003, Kim et al 2004, Mazzocchi et al 2004, Zhang et al 2004b, Maccarinelli et al 2005. There is evidence to suggest that a similar system could exist in female hormone-dependent cancers, such as breast cancer.…”
Section: Introductionmentioning
confidence: 99%